Session of narratives - Maria Auxiliadora Craice De Benedetto; Natália Cristina Zorzenon; Marcelo Levites; Graziela Moreto; Deborah S. O. Garcia; Pablo González Blasco; Débora de Andrade (O Mundo da Saúde)
The 14th Congress of SOBRAMFA began with a session of narratives, which took place before the official opening. This activity was an opportunity for participants – doctors and medical students – to share emergent histories of teaching and the practice of Medicine. Moving or illustrative narratives were presented and it was demonstrated that the storyteller that exists inside each human being has not died. The practice of Medicine in its full magnitude, in other words, as Science and Art, does not ignore the stories experienced in life and told by doctors, patients, students and teachers. This informal event helped understanding the reason why narratives are being increasingly used as a therapeutic, palliative and educational instrument.